What's that noise? Analysing sentiment-based variation in central bank communication - Bernd Hayo; Johannes Zahner (Philipps-University Marburg, School of Business and Economics, 2022)
To which degree can variation in sentiment-based indicators of central bank communication be attributed to changes in macroeconomic, financial, and monetary variables; idiosyncratic speaker effects; sentiment persistence; and random "noise" ? Using the Loughran and McDonald (2011) dictionary on a text corpus containing more than 10,000 speeches and press statements, we construct sentiment-based indicators for the ECB and the Fed. An analysis of variance (ANOVA) shows that sentiment is strongly persistent and influenced by speaker-specific effects. With about 80% of the variation in sentiment being due to noise, our findings cast doubt on the reliability of conclusions based on variation in dictionary-based indicators.
Keywords: C55; E58; E61; Z13; 330; Sentiment index; monetary policy; central banks; Loughran and McDonald (2011) dictionary; information content of sentiment indices